(untitled) (Cambridge, 2014)
This best-selling textbook addresses the full scope of language, from the traditional subjects of structural linguistics (relating to sound, form, meaning and language change) to the more specialised subjects of contextual linguistics (including discourse, dialect variation, language and culture, and the politics of language). There are also separate chapters on language and the brain, computational linguistics, writing, and first and second language learning.
Keywords: Language and languages,Linguistics